Preparation method of high-strength and high-conductivity copper-silver-carbon composite material
The carbon material is uniformly dispersed in copper-silver alloy by semi-solid stirring casting method, which solves the problems of uneven dispersion of carbon materials and dislocation accumulation, improves the mechanical and conductive properties of copper-silver carbon composite materials, and reduces production costs.
Patent Information
- Application Number
- CN202411291744.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-14
AI Technical Summary
In the prior art, the problem of uniform dispersion of carbon materials in copper-silver carbon composites in metal substrates has not been effectively solved, resulting in a decrease in conductivity, and the dislocation accumulation generated during processing affects the mechanical properties, increasing the silver content is high.
Using semi-solid stirring casting method, the surface oxide layer of copper powder and silver particles is removed by pretreatment, and the semi-solid copper-silver alloy melt is melted at high temperature, and mechanically stirred under vacuum to add carbon material to achieve uniform dispersion of carbon material. and solid-phase particles are suspended to reduce pores and shrinkage defects, and improve mechanical properties and electrical conductivity.
The uniform distribution of carbon materials in copper-silver alloy is achieved, the mechanical properties and electrical conductivity of composite materials are improved, production costs are reduced, and the comprehensive performance is achieved.
Smart Images

Figure CN119265445A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-strength and high-conductivity copper-silver-carbon composite materials, and in particular to a production method of a high-strength and high-conductivity copper-silver-carbon composite material. Background Art
[0002] The magnetic field winding coil conductor material must have both high strength and high conductivity. It is usually required to have a strength greater than 700MPa and a conductivity greater than 75% IACS. Currently, the main material that meets these requirements is copper-silver alloy. Compared with other alloys, copper-silver alloy has a better matching relationship between mechanical properties and conductivity.
[0003] This is because both Cu and Ag have face-centered cubic crystal structures. After appropriate deformation and heat treatment processes, such as tensile deformation and intermediate heat treatment, the copper-silver alloy has high strength. At the same time, since no additional scattering is introduced, it can still maintain good conductivity. Studies have shown that after adding silver, the tensile strength of copper-silver alloys with a silver content of <8wt% is increased to 400-800MPa, and the conductivity is reduced to 60%-90% IACS compared to pure copper.
[0004] As the requirements for magnetic field strength continue to increase, the strength and conductivity need to be further improved to meet the requirements. However, copper-silver alloy is a typical work-hardening alloy. To further improve the mechanical properties, it is often necessary to perform severe plastic processing, which will cause dislocation accumulation during the processing. The greater the processing rate, the greater the corresponding dislocation accumulation density, and the conductivity will decrease.
[0005] Although increasing the silver content can improve mechanical properties, since Ag is more expensive than Cu, it is of great significance to improve the overall performance without increasing the Ag content. Most scholars have added additional elements such as Zr and Sc to Cu-Ag alloys to regulate the structure. Although this can improve the tensile strength, the serious defects formed inside the material lead to a significant decrease in conductivity.
[0006] At present, the material is strengthened by adding second phase particles into the matrix, which has the least effect on conductivity. Therefore, finding a suitable additive phase to enable Cu-Ag alloy to obtain high strength while maintaining good conductivity has gradually become the focus of research.
[0007] Carbon materials are increasingly being used in composite materials, such as graphene and carbon nanotubes, due to their outstanding features such as light weight, excellent physical properties, high strength, thermal stability and high conductivity. A large number of experiments have shown that graphene has a good effect of enhancing the mechanical properties of metal materials.
[0008] However, the quality, distribution and integrity of the carbon material in the matrix seriously affect the electrical conductivity of the composite material. One of the problems to be solved is the uniform dispersion of the carbon material in the metal matrix. Chinese patents with patent publication numbers CN108677040, CN108425033, CN108570574, CN108611521 and CN108342609 respectively disclose different preparation methods of adding carbon materials to copper-based alloy composite materials, wherein pure copper, pure silver ingots, pure copper powder, pure silver powder and graphene powder are alloyed by argon protection melt, and the alloy melt in liquid physical state is stirred by mechanical stirring, and the alloy melt temperature is reduced, heat-insulated, cast and post-processed to prepare the composite material.
[0009] However, in the above-mentioned patented technologies, there is a problem of carbon material floating during the stirring of the liquid alloy solution, which makes it impossible for the carbon material to be fully distributed in the alloy solution. The above-mentioned patented technologies do not disclose how to solve the problem of carbon material floating, resulting in the inability to directly prepare copper-silver-carbon composite materials with good dispersion in the actual production process. Summary of the invention
[0010] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a carbon material reinforced copper-silver alloy material by using a semi-solid stirring casting method. The method can improve the problem that the carbon material is difficult to disperse evenly when floating in a metal solution, and achieve uniform distribution of the carbon material. By adding a carbon material to provide a high conductive channel to enhance electron transmission and improve conductivity, the composite material has excellent comprehensive properties. The method is simple to prepare and is conducive to large-scale industrial production.
[0011] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a high-strength and high-conductivity copper-silver-carbon composite material, comprising the following steps:
[0012] Step 1: pretreatment to remove the surface oxide layer of copper powder and silver particles;
[0013] The pretreatment specifically includes a treatment for removing the oxide layer. The treatment for removing the oxide layer is to place the copper powder and the silver particles in a tube furnace respectively, and heat them in a hydrogen and argon atmosphere to remove the oxide layer on the surface of the copper powder and the silver particles.
[0014] Before removing the oxide layer, the copper powder and the silver particles are respectively subjected to ultrasonic cleaning, and the copper powder and the silver particles are respectively put into an ultrasonic cleaning machine for ultrasonic cleaning, and then dried;
[0015] Then, the copper powder and silver particles are placed in a tube furnace to remove the oxide layer. The temperature of the tube furnace is raised to 200-800°C, and then a mixed atmosphere of hydrogen and argon is introduced and kept warm for 1-3 hours to remove the oxide layer on the surface of the copper powder and silver particles, and then the furnace is cooled to room temperature.
[0016] After copper powder is put into an ultrasonic cleaning machine alone, it is sequentially subjected to alcohol ultrasonic cleaning treatment, distilled water ultrasonic cleaning treatment and drying treatment, and the cycle is performed multiple times;
[0017] After the silver particles are individually put into an ultrasonic cleaning machine, they are sequentially subjected to alcohol ultrasonic cleaning treatment, distilled water ultrasonic cleaning treatment and drying treatment, which are repeated multiple times;
[0018] Alcohol ultrasonic cleaning is to first add alcohol to the ultrasonic cleaning machine, then start the ultrasonic wave of the ultrasonic cleaning machine to perform ultrasonic cleaning,
[0019] The distilled water ultrasonic cleaning treatment is to first add distilled water into the ultrasonic cleaning machine, and then start the ultrasonic wave of the ultrasonic cleaning machine to perform ultrasonic cleaning to achieve distilled water ultrasonic cleaning.
[0020] Step 2, smelting treatment, putting copper powder and silver particles into the crucible of a vacuum melting furnace, the molar ratio of copper powder to silver particles is 400-100:1, and performing vacuum high-temperature smelting. During the smelting process, the vacuum degree (air pressure) of the vacuum melting furnace is maintained below 5Mpa to obtain a copper-silver alloy melt.
[0021] Step 3, transforming and maintaining the physical form, by controlling the temperature of the vacuum melting furnace to reduce and maintain the temperature of the copper-silver alloy melt, and maintaining the temperature of the copper-silver alloy melt within the semi-solid temperature range corresponding to the copper-silver alloy melt. The temperature of the copper-silver alloy melt is reduced to 1000-1080°C, the physical form of the copper-silver alloy melt is transformed from liquid to semi-solid, and the temperature of the copper-silver alloy melt is maintained at 1000-1080°C after the copper-silver alloy melt is transformed into a semi-solid state, and a heat preservation treatment is performed to keep the physical form of the copper-silver alloy melt in a semi-solid state, and then a stirring paddle is used to perform turbulent stirring on the semi-solid copper-silver alloy melt under vacuum.
[0022] Step 4, adding carbon material while performing turbulent stirring under vacuum and continuing stirring, adding carbon material at an input ratio of 0.1 to 0.5 mol% by mole, the carbon material including but not limited to graphene, carbon nanotubes, graphite and carbon quantum dots, maintaining the temperature of the copper-silver alloy melt at 1000 to 1080° C., maintaining the physical form of the copper-silver alloy melt in a semi-solid state during stirring, so that the carbon material can be uniformly dispersed and suspended in the semi-solid copper-silver alloy melt, and the semi-solid copper-silver alloy melt holds and stabilizes the carbon material dispersed therein in the copper-silver alloy melt;
[0023] Before stirring, the surface of the stirring paddle is coated with high temperature glue and then the stirring paddle is inserted into the semi-solid copper-silver alloy melt. The copper-silver alloy melt is mechanically stirred by the stirring paddle, and the rotation speed of the stirring paddle is 800-1200rpm.
[0024] Step 5, preheating the casting mold at a preheating temperature of 400-500° C., casting the copper-silver alloy melt into the preheated casting mold, and obtaining the copper-silver-carbon composite material after demolding.
[0025] In order to solve the shortcomings existing in the prior art, the present invention adds a small amount of carbon material to the alloy material, adopts vacuum induction melting, and uses an innovative semi-solid stirring process to ensure that the carbon material has high dispersion and relatively complete structure in the matrix. The microstructure of the semi-solid alloy has the characteristics of solid phase particles suspended in the liquid phase matrix. The uniformly dispersed carbon material can be effectively loaded under the action of tensile stress, and the carbon material located at the grain boundary of the copper-silver alloy plays a dislocation pinning role, hindering the movement and migration of dislocations, thereby enhancing the mechanical properties of the composite material. Semi-solid forming can effectively reduce the defects of pores and shrinkage cavities in the casting process, and improve the compactness and mechanical properties of the casting. The carbon material achieves a strong interface bonding with the matrix, and with the help of its own high electron mobility characteristics, the overall charge transfer rate is improved, thereby improving the conductivity.
[0026] Compared with the prior art, the present invention has the advantages that the present invention not only solves the problem of uneven dispersion of carbon materials caused by carbon floating, but also prepares a copper-silver-carbon composite material with lower cost and relatively better comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the grain metallographic diagram of Example 1.
[0028] Figure 2 This is a physical picture of Example 1.
[0029] Figure 3 for Figure 2 Left view of the actual picture. DETAILED DESCRIPTION
[0030] Example 1
[0031] A method for preparing a high-strength and high-conductivity copper-silver-carbon composite material. Figures 1 to 3 As shown, the carbon material added in this embodiment is graphene powder, which includes the following steps:
[0032] Step 1, weigh high-purity copper and silver and place them in an ultrasonic cleaning machine, and use alcohol and distilled water to wash them 3 times, 10 minutes each time, to remove surface pollutants and grease. After drying, weigh 16 mol of high-purity copper and 0.18 mol of silver, with a copper-silver material molar ratio of 800:9. Place them in a tube furnace in H2 (50 sccm / min), Ar (500 sccm / min) atmosphere, keep them at 350°C for 1h to remove the surface oxide layer, and then cool them to room temperature with the furnace.
[0033] Step 2: Place the copper block and the silver block in a vacuum induction furnace, and start the smelting equipment for smelting when the vacuum degree reaches below 5 MPa. Set the temperature to 1100° C. and the smelting time to 2 h.
[0034] Step 3, when the temperature of the alloy melt drops to a semi-solid temperature of 1000-1080°C, add graphene powder, with the graphene amount being 0.1 mol. Then insert a conventional single stirring paddle, which needs to be preheated at 400-500°C for at least 30 minutes before insertion. The stirring paddle must be coated with high-temperature glue before use to prevent contamination of the molten pool environment; the speed of mechanical stirring is 1000 rpm, and stirring is performed for 5-15 minutes.
[0035] Step 4: After all the micron graphene particles are dispersed in the melt, the melt is cast into an iron mold preheated at 400-500° C. for 1-2 hours, and then cooled to room temperature to obtain a sample 1 copper-silver graphene composite material. Figures 1 to 3 As shown in Table 1, the conductivity (% IACS), elongation (%) and tensile strength (Mpa) of sample 1 were tested and obtained.
[0036] Example 2
[0037] A method for preparing a high-strength and high-conductivity copper-silver-carbon composite material, wherein the carbon material added in this embodiment is carbon nanotube powder, comprises the following steps:
[0038] Step 1, weigh high-purity copper and silver and place them in an ultrasonic cleaning machine, and use alcohol and distilled water to wash them 3 times, 10 minutes each time, to remove surface pollutants and grease. After drying, weigh 16 mol of high-purity copper and 0.18 mol of silver, with a copper-silver material ratio of 800:9. Place them in a tube furnace in H2 (50 sccm / min), Ar (500 sccm / min) atmosphere, keep them at 350°C for 1 hour to remove the surface oxide layer, and then cool them to room temperature with the furnace.
[0039] Step 2: Place the copper block and the silver block in a vacuum induction furnace, and start the smelting equipment for smelting when the vacuum degree reaches below 5 MPa. Set the temperature to 1100° C. and the smelting time to 2 h.
[0040] Step 3, when the temperature of the alloy melt drops to a semi-solid temperature of 1000-1080°C, add carbon nanotube powder, with 0.1 mol of carbon nanotubes. Then insert a conventional single stirring paddle, which needs to be preheated at 400-500°C for at least 30 minutes before insertion. The stirring paddle must be coated with high-temperature glue before use to prevent contamination of the molten pool environment; the speed of mechanical stirring is 1000 rpm, and stirring is performed for 5-15 minutes.
[0041] Step 4, after all the micron carbon nanotube particles are dispersed in the melt, cast it into an iron mold preheated at 400-500°C for 1-2h, and cool it to room temperature to obtain sample 2 copper-silver carbon nanotube composite material. The conductivity (%IACS), elongation (%) and tensile strength (Mpa) of sample 2 are tested respectively, as shown in Table 1.
[0042] Example 3
[0043] A method for preparing a high-strength and high-conductivity copper-silver-carbon composite material, wherein the carbon material added in this embodiment is carbon-carbon quantum dots, comprises the following steps:
[0044] Step 1, weigh high-purity copper and silver and place them in an ultrasonic cleaning machine, and use alcohol and distilled water to wash them 3 times, 10 minutes each time, to remove surface pollutants and grease. After drying, weigh 16 mol of high-purity copper and 0.18 mol of silver, with a copper-silver material ratio of 800:9. Place them in a tube furnace in H2 (50 sccm / min), Ar (500 sccm / min) atmosphere, keep them at 350°C for 1 hour to remove the surface oxide layer, and then cool them to room temperature with the furnace.
[0045] Step 2: Place the copper block and the silver block in a vacuum induction furnace, and start the smelting equipment for smelting when the vacuum degree reaches below 5 MPa. Set the temperature to 1100° C. and the smelting time to 2 h.
[0046] Step 3, when the temperature of the alloy melt drops to a semi-solid temperature of 1000-1080°C, add carbon quantum dots, with the amount of carbon quantum dots being 0.1 mol. Then insert a conventional single stirring paddle, which needs to be preheated at 400-500°C for at least 30 minutes before insertion. The stirring paddle must be coated with high-temperature glue before use to prevent contamination of the molten pool environment; the speed of mechanical stirring is 1000 rpm, and stirring is performed for 5-15 minutes.
[0047] Step 4, after all the carbon quantum dot particles are dispersed in the melt, cast them into an iron mold preheated at 400-500°C for 1-2h, and then cooled to room temperature to obtain sample 3 copper-silver carbon quantum dot composite material. The conductivity (%IACS), elongation (%) and tensile strength (Mpa) of sample 3 were tested, as shown in Table 1.
[0048] Example 4
[0049] A method for preparing a pure copper material comprises the following steps:
[0050] Step 1, weigh high-purity copper in an ultrasonic cleaning machine, and use alcohol and distilled water to wash 3 times, 10 minutes each time, to remove surface pollutants and grease. After drying, weigh 16 mol of high-purity copper, place it in a tube furnace in H2 (50 sccm / min), Ar (500 sccm / min) atmosphere, keep it at 350°C for 1 hour to remove the surface oxide layer, and then cool it to room temperature with the furnace.
[0051] Step 2: Place the copper block inside the vacuum induction furnace, and start the smelting equipment for smelting when the vacuum degree reaches below 5 MPa. Set the temperature to 1100° C. and the smelting time to 2 h.
[0052] Step 3, insert a conventional single stirring paddle, which needs to be preheated to 400-500℃ for at least 30 minutes before insertion. The stirring paddle must be coated with high-temperature glue before use to prevent contamination of the molten pool environment; the speed of mechanical stirring is 1000rpm, and stirring is performed for 5-15 minutes.
[0053] Step 4, casting in an iron mold preheated at 400-500°C for 1-2h, and cooling to room temperature to obtain a copper ingot of sample 4. The conductivity (%IACS), elongation (%) and tensile strength (Mpa) of sample 4 were tested respectively, as shown in Table 1.
[0054] Example 5
[0055] A method for preparing a copper-silver composite material comprises the following steps:
[0056] Step 1, weigh high-purity copper and silver and place them in an ultrasonic cleaning machine, and use alcohol and distilled water to wash them 3 times, 10 minutes each time, to remove surface pollutants and grease. After drying, weigh 16 mol of high-purity copper and 0.18 mol of silver, with a copper-silver material ratio of 800:9. Place them in a tube furnace in H2 (50 sccm / min), Ar (500 sccm / min) atmosphere, keep them at 350°C for 1 hour to remove the surface oxide layer, and then cool them to room temperature with the furnace.
[0057] Step 2: Place the copper block and the silver block in a vacuum induction furnace, and start the smelting equipment for smelting when the vacuum degree reaches below 5 MPa. Set the temperature to 1100° C. and the smelting time to 2 h.
[0058] Step 3: When the temperature of the alloy melt drops to a semi-solid temperature of 1000-1080°C, insert a conventional single stirring paddle. The stirring paddle needs to be preheated at 400-500°C for at least 30 minutes before insertion. The stirring paddle must be coated with high-temperature glue before use to prevent contamination of the molten pool environment; the speed of mechanical stirring is 1000rpm, and stirring is performed for 5-15 minutes.
[0059] Step 4, casting in an iron mold preheated at 400-500° C. for 1-2 hours, and cooling at room temperature to obtain a copper-silver composite material.
[0060] Comparative Example 1
[0061] The Chinese patent with the patent publication number CN108677040 has a silver mass fraction of 24%.
[0062] A method for preparing a copper-based alloy blank with good electrical conductivity comprises the following steps:
[0063] (1) using pure copper ingot, pure silver ingot, pure silver powder and graphene powder as raw materials, wherein the composition is 87wt% of pure copper ingot, 10wt% of pure silver ingot, 2wt% of pure silver powder and 1wt% of graphene powder, with a total amount of 100%, wherein the diameter of the pure silver powder is 0.05-100μm, and the surface oxide is removed after reduction treatment;
[0064] (2) firstly, pure copper ingots and pure silver ingots are mixed and heated to 1100°C to melt them into an alloy melt. After keeping the temperature for 10 minutes, argon gas is used to protect the melt surface, and pure silver powder and graphene powder are added. The alloy melt is fully stirred for 1-5 minutes by mechanical stirring. At the same time, the temperature of the alloy melt is reduced to 1000°C and kept for 10-15 minutes to make the alloy melt solidify rapidly and form a melt with a semi-solid mixed structure;
[0065] (3) The semi-solid mixed structure melt is poured into a mold cooled by circulating water to form an ingot, and then cooled to room temperature at a rate of 80° C. / min to obtain a copper-based alloy billet.
[0066] Comparative Example 2
[0067] The Chinese patent with the patent publication number CN108425033 has a silver mass fraction of 24%.
[0068] A method for preparing a high-yield strength copper-based alloy blank comprises: mixing 75wt% pure copper ingots and 14wt% pure silver ingots and heating them to 1050-1700°C to melt them into an alloy melt; keeping the mixture warm for 10 minutes, using argon to protect the melt surface, adding 10wt% pure silver powder and 1wt% graphene powder, stirring the alloy melt for 1-5 minutes by mechanical stirring, reducing the temperature of the alloy melt to 900-1600°C, and keeping the mixture warm for 10-15 minutes to rapidly solidify the alloy melt and form a semi-solid mixed structure melt; subsequently, pouring the semi-solid mixed structure melt into a mold cooled by circulating water to form an ingot, cooling it to room temperature at a speed of 50-200°C / min to obtain a copper-based alloy blank; heating the copper-based alloy blank to 7 00-720℃, keep warm for 1h, distribute the ingot along three orthogonal directions of longitudinal, transverse and axial for forging, with a forging reduction of 20-40% in each direction, then air-cool the forging billet to room temperature, heat the forging billet to 500℃ and keep warm for 1h, distribute the forging along three orthogonal directions of longitudinal, transverse and axial forging, with a forging reduction of 10-30% in each direction, then air-cool the forging billet to room temperature, heat the forging billet to 400℃ and keep warm for 1h, distribute the forging along three orthogonal directions of longitudinal, transverse and axial forging, with a forging reduction of 10-30% in each direction, then air-cool the forging billet to room temperature, heat the forging billet to 300℃ and keep warm for 1h, distribute the forging along three orthogonal directions of longitudinal, transverse and axial forging, with a forging reduction of 10-30% in each direction.
[0069] Comparative Example 3
[0070] The Chinese patent with the patent publication number CN108570574 has a silver mass fraction of 30%.
[0071] A method for preparing a copper-based alloy blank containing graphene comprises the following steps:
[0072] (1) Using pure copper ingot, pure silver ingot, pure copper powder and graphene powder as raw materials, the composition is 65wt% of pure copper ingot, 30wt% of pure silver ingot, 4wt% of pure copper powder and 1wt% of graphene powder, wherein the diameter of the pure copper powder is 50-100μm, and the surface oxide is removed after reduction treatment;
[0073] (2) First, pure copper ingots and pure silver ingots are mixed and heated to 1050°C to melt them into an alloy melt. After keeping the temperature for 10 minutes, pure copper powder and graphene powder are added, and the alloy melt is fully stirred for 1-5 minutes by mechanical stirring. At the same time, the temperature of the alloy melt is reduced to 900°C and kept for 10-15 minutes to allow the alloy melt to solidify rapidly and form a melt with a semi-solid mixed structure.
[0074] (3) The semi-solid mixed structure melt is poured into a mold cooled by circulating water to form an ingot, and then cooled to room temperature at a rate of 50-200° C. / min to obtain a high-strength and high-conductivity copper-based alloy billet containing graphene.
[0075] Comparative Example 4
[0076] The Chinese patent with the patent publication number CN108611521 has a silver mass fraction of 12%.
[0077] A method for preparing a copper-based alloy blank comprises the following steps:
[0078] (1) Using pure copper ingot, pure silver ingot, pure copper powder and graphene powder as raw materials, the composition is 85wt% of pure copper ingot, 12wt% of pure silver ingot, 2wt% of pure copper powder and 1wt% of graphene powder;
[0079] (2) First, pure copper ingots and pure silver ingots are mixed and heated to 1100°C to melt them into an alloy melt. After keeping the temperature for 10 minutes, argon gas is used to protect the melt surface, and pure copper powder and graphene powder are added. The alloy melt is fully stirred for 3 minutes. At the same time, the temperature of the alloy melt is reduced to 900°C and kept for 10 minutes to allow the alloy melt to solidify rapidly and form a melt with a semi-solid mixed structure.
[0080] (3) The semi-solid mixed structure melt is poured into a mold cooled by circulating water to form an ingot, and then cooled to room temperature at a rate of 80° C. / min to obtain a copper-based alloy billet.
[0081] The conductivity, elongation and tensile strength of samples 1 to 4 of the embodiments of the present invention were respectively detected, as shown in Table 1. By comparison, it can be seen that the molar ratio of silver in the present invention is 0.18%, and the molar ratio of carbon material is 0.1%, but the conductivity of Examples 1 to 4 is greater than the maximum value of 90% IACS recorded in Comparative Examples 1 to 4, and has good elongation. This is because the present invention solves the problem of uneven dispersion of carbon materials caused by carbon floating, and because the present invention greatly reduces the input ratio of relatively high-priced silver, it can also reduce production costs, thereby obtaining a copper-silver-graphite alloy material with lower production costs and relatively better comprehensive performance.
[0082]
[0083] Table 1 - Comparison table of experimental data.
Claims
1. A method for preparing a high-strength and high-conductivity copper-silver-carbon composite material, characterized in that: The following steps are included: Step 1: pretreatment to remove the surface oxide layer of copper powder and silver particles; Step 2, smelting treatment, putting copper powder and silver particles into a crucible of a vacuum melting furnace, wherein the mass molar ratio of silver is less than 5%, and performing vacuum high-temperature smelting to obtain a copper-silver alloy melt; Step 3, transforming and maintaining the physical form, lowering the temperature of the copper-silver alloy melt, transforming the physical form of the copper-silver alloy melt from a liquid state to a semi-solid state, performing heat preservation treatment to keep the physical form of the copper-silver alloy melt in a semi-solid state, and then using a stirring paddle to perform turbulent stirring on the semi-solid copper-silver alloy melt under vacuum; Step 4, adding carbon material while performing turbulent stirring under vacuum and continuing stirring, wherein the mass molar ratio of the carbon material is less than 1%, so that the carbon material can be uniformly dispersed and suspended in the semi-solid copper-silver alloy melt, and the semi-solid copper-silver alloy melt can hold and stabilize the carbon material dispersed therein in the copper-silver alloy melt; Step 5, casting the copper-silver alloy melt into a casting mold that has been preheated, and obtaining a copper-silver-carbon composite material after demolding.
2. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 1, characterized in that: The step 3 is to reduce and maintain the temperature of the copper-silver alloy melt by controlling the temperature of the vacuum melting furnace. In the step 3 and the step 4, the temperature of the copper-silver alloy melt is maintained within a semi-solid temperature range corresponding to the copper-silver alloy melt.
3. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 1, characterized in that: In the step 2, the molar mass ratio of copper powder to silver particles is 400 to 100:
1. In the step 4, the carbon material is added at a ratio of 0.1 to 0.5 mol% by molar mass.
4. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 1, characterized in that: The carbon material includes but is not limited to graphene, carbon nanotubes, graphite and carbon quantum dots.
5. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 3, characterized in that: In step 3, the temperature of the copper-silver alloy melt is reduced to 1000-1080° C., and the temperature of the copper-silver alloy melt is maintained at 1000-1080° C. after the copper-silver alloy melt is transformed into a semi-solid state. In the step 4, the temperature of the copper-silver alloy melt is maintained at 1000-1080° C., and the physical state of the copper-silver alloy melt is maintained in a semi-solid state during the stirring process.
6. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 1, characterized in that: In the step 4, the surface of the stirring paddle is first coated with high temperature glue and then the stirring paddle is inserted into the semi-solid copper-silver alloy melt, and the copper-silver alloy melt is mechanically stirred by the stirring paddle, and the rotation speed of the stirring paddle is 800-1200 rpm.
7. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 1, characterized in that: The step 2 is to maintain the vacuum degree of the vacuum melting furnace below 5 MPa during the melting process. The step 4 is to preheat the casting mold at a temperature of 400 to 500°C.
8. A method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to any one of claims 1 to 7, characterized in that: In the step 1, the pretreatment includes removing the oxide layer. The oxide layer removal treatment is to place the copper powder and the silver particles respectively inside a tubular furnace, and heat them under a hydrogen and argon atmosphere to remove the oxide layer on the surface of the copper powder and the silver particles.
9. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 8, characterized in that: In the step 1, the copper powder and the silver particles are respectively subjected to ultrasonic cleaning treatment before the oxide layer removal treatment, and the copper powder and the silver particles are respectively put into an ultrasonic cleaning machine for ultrasonic cleaning treatment, and then dried; Then, the copper powder and silver particles are placed in a tube furnace to remove the oxide layer. The temperature of the tube furnace is raised to 200-800°C, and then a mixed atmosphere of hydrogen and argon is introduced and kept warm for 1-3 hours to remove the oxide layer on the surface of the copper powder and silver particles, and then the furnace is cooled to room temperature.
10. The method for preparing a high-strength and high-conductivity copper-silver-carbon composite material according to claim 9, characterized in that: Step 1, After the copper powder is put into the ultrasonic cleaning machine alone, it is sequentially subjected to alcohol ultrasonic cleaning treatment, distilled water ultrasonic cleaning treatment and the drying treatment, and the cycle is performed multiple times; After the silver particles are individually put into the ultrasonic cleaning machine, alcohol ultrasonic cleaning treatment, distilled water ultrasonic cleaning treatment and the drying treatment are sequentially performed, and the cycle is performed multiple times; Alcohol ultrasonic cleaning is to first add alcohol to the ultrasonic cleaning machine, then start the ultrasonic wave of the ultrasonic cleaning machine to perform ultrasonic cleaning, The distilled water ultrasonic cleaning treatment is to first add distilled water into the ultrasonic cleaning machine, and then start the ultrasonic wave of the ultrasonic cleaning machine to perform ultrasonic cleaning to achieve distilled water ultrasonic cleaning.
Citation Information
Patent Citations
Preparation method of high-intensity and high-conductivity Cu-Nb alloy billet
CN106676313A
Preparing method of copper-based alloy billet with high conductivity,
CN108677040A
Method for synthesizing copper-silver alloy, method for forming conduction part, copper-silver alloy, and conduction part
US20200381136A1